Engraving a lasting change in the community: a qualitative inquiry on active student volunteers' experience in groundups - Phoon, Phui Yi (Nanyang Technological University, 2024)
As of present, the local literature on the groundups landscape is scarce. Aside from the Groundup Initiative Study conducted in 2023, no other researchers have attempted to look into the experience of groundup volunteers. Instead, there has been a plethora of studies done on students’ volunteering experience and volunteer retention. This paper strives to address this gap in literature by conducting a qualitative inquiry into students’ volunteering experience with groundups. The study adopts a Model of Young People’s Sustained Volunteerism and interviewed three students on their volunteering journey. From their interviews, a new ecological model is proposed in explaining how volunteer motivation, group integration, identity, satisfaction, and the relationships with groundup members interact with one another to retain student volunteers.